Development Strategy For Transfer Of Oil Palm Land Functions To Rice Rice Land - Timbul Rasoki; Ana Nurmalia; Lina Asnamawati (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The agricultural sector plays an important role in food sovereignty. In Indonesia, the conversion of agricultural land to non-agricultural land is rife, while in Mukomuko Regency there has been a change of function from plantation land to rice fields. This supports the district's vision and mission regarding food sovereignty. The purpose of this study was to analyze and formulate a strategy for developing land conversion from oil palm to lowland rice. This study was analyzed using descriptive and quantitative methods using SWOT analysis. The results showed that the decrease in the value of internal factors obtained a greater value of strength (S) (+). From the reduction of external factors, the opportunity value (O) is also greater (+). So that the right strategy to be used in increasing the conversion of oil palm agricultural land into lowland rice in Mukomuko Regency, Bengkulu Province is the following strategy (SO); increasing the conversion of land to lowland rice, increasing marketing to areas that do not have the potential for lowland rice, utilizing and increasing the use of technology to increase productivity and efficiency after land conversion, increasing farmer group activities and continuing to coordinate with the government (extension) regarding obstacles faced such as simultaneous planting , pests and so on.